2019
DOI: 10.1021/acs.chemmater.9b00743
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanism of Li10GeP2S12-type Lithium Superionic Conductors in a Li–Sn–Si–P–S System

Abstract: Crystal structures of Li 1 0 GeP 2 S 1 2 (LGPS)-type Li 10+δ [Sn y Si 1−y ] 1+δ P 2−δ S 12 (Li 4−x [Sn y Si 1−y ] 1−x P x S 4 ) solid electrolytes were analyzed by Rietveld refinement using neutron diffraction data. Maximum entropy method analysis was performed to visualize the distribution of lithium along the c-axis via the Li1−Li3 sites, which indicated one-dimensional (1D) lithium diff usion for all the ex amined compositions. The Li 10.35 Sn 0.27 Si 1.08 P 1.65 S 12 (Li 3.45 Sn 0.09 Si 0.36 P 0.55 S 4 ) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…[ 32 ] In fact, the widely spread lithium distribution has been visualized using MEM. [ 13,32,57,84,85 ]…”
Section: Structurementioning
confidence: 99%
See 4 more Smart Citations
“…[ 32 ] In fact, the widely spread lithium distribution has been visualized using MEM. [ 13,32,57,84,85 ]…”
Section: Structurementioning
confidence: 99%
“…highlighted changes in the conduction mechanism from 1D‐like to 3D‐like, and suggested that a 3D Li distribution at lower temperature may help improve the conductivity. [ 57 ] Although this has not been achieved for Li 9.81 Sn 0.81 P 2.19 S 12 (5 × 10 −3 S cm −1 at 298 K) shown in Figure 10d, the introduction of Si provides Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 [ 84 ] with 3D Li distribution and a higher conductivity of 1.1 × 10 −2 S cm −1 (Figure 10e). Moreover, a conductivity of 2.5 × 10 −2 S cm −1 has been achieved for the Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 system with 3D Li distribution (Figure 10f).…”
Section: Structurementioning
confidence: 99%
See 3 more Smart Citations